Respiratory Syncytial Virus associated hospitalisations in children up to 6 years of age in Italy: a systematic review - Bechini, Angela; Salvati, Cristina; Bonito, Benedetta; Del Riccio, Marco; Stancanelli, Enrica; Bruschi, Mario; Ionita, Giulia; Iamarino, Johanna; Bentivegna, Davide; Buscemi, Primo; Ciardi, Giulia; Cosma, Claudia; et al. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Introduction. Respiratory syncytial virus is a leading cause of respiratory hospitalisations in infants. This systematic review (registration number: CRD42021248309) aims to synthesise the available evidence on Respiratory Syncytial Virus-related hospitalisations among children aged 0 to 6 years in Italy. Methods. The literature search was conducted on PubMed, Embase, Scopus, and International HTA, covering the period from January 2000 to July 2022, with a focus on studies that reported information on Respiratory Syncytial Virus-associated hospitalisation in children aged 0-6 years in Italy. Results. Eight articles were included after screening 20,845 records. These retrospective studies reported that most hospitalisations were among those